2008
DOI: 10.2135/cropsci2007.05.0310
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Timing Effects on Estimates of Rumen Degradable Protein from Alfalfa Forages

Abstract: Alfalfa (Medicago sativa L.) proteins ingested by dairy cows typically degrade at rapid rates and exhibit extensive ruminal degradability. Although the effects of conservation method (hay or silage) on these characteristics have been evaluated extensively, agronomic factors, such as harvest timing, have not. Our objective was to quantify rumen degradable protein (RDP) for ‘Affinity’ alfalfa harvested over a range of ages (0, 5, 10, 15, and 20 d following Stage 2) within each of four harvest periods (spring, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(51 reference statements)
4
9
0
Order By: Relevance
“…The concentration of CP in the total herbage and leaf‐to‐stem ratio (LSR) are expected to respond similarly to most agricultural practices, and their decline has been attributed to advancing maturity (Buxton et al, 1985; Halim et al, 1989; Lloveras et al, 2008). A general decline of CP as time progresses from an early bud stage to late flowering has been reported by several authors (Gabrielsen et al, 1985; Hintz and Albrecht, 1991; Coblentz et al, 2008). In addition, it has been clearly demonstrated that a decline of CP with maturity is accompanied by a decrease in the concentrations of both ash and ether extract (EE) in the alfalfa forage (Darlington and Hershberger, 1968; Dien et al, 2006).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The concentration of CP in the total herbage and leaf‐to‐stem ratio (LSR) are expected to respond similarly to most agricultural practices, and their decline has been attributed to advancing maturity (Buxton et al, 1985; Halim et al, 1989; Lloveras et al, 2008). A general decline of CP as time progresses from an early bud stage to late flowering has been reported by several authors (Gabrielsen et al, 1985; Hintz and Albrecht, 1991; Coblentz et al, 2008). In addition, it has been clearly demonstrated that a decline of CP with maturity is accompanied by a decrease in the concentrations of both ash and ether extract (EE) in the alfalfa forage (Darlington and Hershberger, 1968; Dien et al, 2006).…”
supporting
confidence: 60%
“…Under the same environmental conditions, the nutritive value of alfalfa forage can vary widely based on the choice of cultivar and harvest management (Julier et al, 2000; Kallenbach et al, 2002; Lamb et al, 2007). Plant maturity stage at harvest has been shown to be a primary factor influencing the chemical composition of alfalfa forage, mainly due to a temporal decrease in the leaves, which are generally more digestible and contain more nutrients, and an increase in stems, which are generally less digestible (Hintz and Albrecht, 1991; Sheaffer et al, 2000; Coblentz et al, 2008).…”
mentioning
confidence: 99%
“…Dry-matter concentrations of condensed tannin (CT), rumen degradable protein as a proportion of crude protein (RDP CP ) and dry matter (RDP DM ), rumen undegradable protein as a proportion of dry matter (RUP DM ), rumen degradable dry matter (RDDM), and true degradable dry matter (TDDM) in herbage sampled from 14 birdsfoot trefoil cultivars and one alfalfa cultivar in 2006. The positive effects of CP concentration on RDP CP and RDP DM and the weak effect of CP on RUP DM also were consistent with previous studies with alfalfa (Coblentz et al, 2008), which does not contain CT in its herbage. Cultivar CT † RDP CP RDP DM RUP DM RDDM TDDM for animal utilization.…”
Section: Degradability Vs Chemical Compositionsupporting
confidence: 91%
“…The negative relationship of RDP CP , and RDP DM with CT and the positive relationship of RUP DM with CT are consistent with previous studies, which found CT limit the degradation of protein in BFT by rumen microflora or commercial proteases (Coblentz and Grabber, 2013;Grabber, 2008;Miller and Ehlke, 1994). The positive effects of CP concentration on RDP CP and RDP DM and the weak effect of CP on RUP DM also were consistent with previous studies with alfalfa (Coblentz et al, 2008), which does not contain CT in its herbage. As illustrated in Fig.…”
Section: Degradability Vs Chemical Compositionsupporting
confidence: 90%
“…The frequency of shoot removal has long been recognized as a key factor in determining alfalfa yield, yield components, forage nutritive value (Kalu and Fick, 1983; Kallenbach et al, 2002; Brink et al, 2010), and stand persistence (Brink and Marten, 1989; Brummer and Bouton, 1991; Ventroni et al, 2010). Several studies documented a decline of nutritive value and increase of alfalfa productivity associated with advancing maturity from early bud to late flowering (Kallenbach et al, 2002; Coblentz et al, 2008; Brink et al, 2010). In addition, it has been shown that harvesting alfalfa frequently during the growing season may have detrimental effects on the stand persistence, determined as plants m −2 (Parsons and Davis, 1960; Macolino et al, 2002; Davies and Peoples, 2003).…”
mentioning
confidence: 99%